1993
DOI: 10.1177/104063879300500319
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Toxicity of Fumonisin in Weanling Pigs

Abstract: Three gilts fed a diet containing 100 mg fumonisin B1/kg for 7 days followed by a diet containing 190 mg/kg for 83 days developed nodular hyperplasia of the liver. These nodules of various diameters were composed of solid sheets or nests of hepatocytes. There were no discernible central veins or portal triads, and the perilobular connective tissue and adjacent parenchyma were compressed. Three other gilts maintained on the same diet for 27-80 days developed severe hepatopathies, but not nodular hyperplasia, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
45
4
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 13 publications
3
45
4
1
Order By: Relevance
“…Kilic and Akay (2008) found that serum TP of rats fed GM maize was lower only compared with rats fed non-GM maize but was similar to that of rats fed a commercial control diet. However, in these studies, mycotoxin contamination was not investigated and it has been shown that mycotoxins could lead to liver damage, and thus reduced serum TP (Casteel et al, 1993). Similar to findings from the present study, the lower serum TP observed by Schrøder et al (2007) in rats did not occur in conjunction with histological or organ weight changes, thus questioning the biological relevance of this alteration.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Kilic and Akay (2008) found that serum TP of rats fed GM maize was lower only compared with rats fed non-GM maize but was similar to that of rats fed a commercial control diet. However, in these studies, mycotoxin contamination was not investigated and it has been shown that mycotoxins could lead to liver damage, and thus reduced serum TP (Casteel et al, 1993). Similar to findings from the present study, the lower serum TP observed by Schrøder et al (2007) in rats did not occur in conjunction with histological or organ weight changes, thus questioning the biological relevance of this alteration.…”
Section: Discussionsupporting
confidence: 64%
“…Elevated serum GGT and changes in nuclei structure were observed in the liver of lambs fed GM maize (Trabalza-Marinucci et al, 2008). Unlike our study, these studies did not completely investigate the potential for contamination of the GM maize, as it has been shown that contaminants such as mycotoxins are known to affect liver histology and liver health indicator enzymes (Casteel et al, 1993). In any case, further work is needed to investigate why these effects were observed in these previous studies.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This F. moniliforme culture material was mixed with com lacking FB 1 , and the resulting mixture was reassayed. The average fumonisin B 1 , B 2 , and B 3 levels in the final corn mixture fed to cattle was 328 FB 1 , 89 ppm FB 2 , and 23 ppm FB 3 .…”
mentioning
confidence: 97%
“…Many nations, including the United States, have maintained piroplasmosis-, dourine-, and glanders-free equine populations for many years. 1,3,6 Four separate complement fixation tests (CFT) are usually conducted for serodiagnostic purposes, 1 CFT for antibodies against each of the infectious agents. 2,3 The OIE also prescribes alternative test methods, and these must be used with sera that produce anticomplementary or otherwise spurious reactions in the CFT.…”
mentioning
confidence: 99%